International financial management : problems, issues, and experiences - Oh, John S. (Greenwich, Conn. : JAI Press, 1983)
The focus of this series of papers is on the concerns of U.S. multinationals regarding the external environment that impacts on exchange rate determination; exchange risk, exposure management and reporting requirements under the current exchange rate regime; and the investment and financing decisions that these internationally expose firms tend to encounter.
Includes bibliographical references and indexes.
hza 27/08/2018
Loans
Keywords: International business enterprises; Foreign exchange; Balance of payments